Starting up - Boland, Michael; Ahmed, Anoar; Video Education Austalasia (Bendigo, Vic. : Video Education Austalasia, 2010)
This program investigates what it takes to be a small business owner, including legal implications, product demand and niche markets, making a business profitable and the importance choosing the correct name for your business
Executive producer, Simon Garner
Voice over: Adam MAttaliano
DVD format
Keywords: Small business -- Australia